Experimental Study on the Property Degradation and Failure Mechanism of Weakly Cemented Sandstone under Dry-Wet Cycles. (18th January 2022) - Song, Zhaoyang; Sun, Lihui; Cheng, Shouye; Liu, Zhiqiang; Tan, Jie; Ning, Fangbo
Abstract : Taking the weakly cemented sandstone of Ordos, China, as the research object, the evolution law between the relative stress of weakly cemented sandstone and the multiparameters of the acoustic emission under different dry-wet cycles was explored, and the critical failure identification mode of weakly cemented sandstone under dry-wet cycle was established. The results show that as the number of dry-wet cycles increases, the wave velocity loss rate gradually increases. Overall, the longitudinal wave loss rate is larger than the shear wave loss rate, indicating that the longitudinal wave is more sensitive to the degradation of weakly cemented sandstone. With an increase in the number of dry-wet cycles, the crack is mainly caused by the main crack penetration failure, and the secondary crack is significantly reduced. The fractal dimension decreases with an increase in the dry-wet cycles and reaches its maximum at 0 dry-wet cycles, which means that 0 dry-wet cycles witness the most complex morphology of fractures within the weakly cemented sandstone. This finding indicates that the dry-wet cycle inhibits the generation and expansion of fractures. The event rate appears to be close to 0 before the rupture, and then the platform oscillates, followed by a sudden increase. The acoustic emission b value is relatively high during the initial stage and then decreases, which is the initial damage process. The elastoplastic phase rises again, the peak stage decreases rapidly, and the weakly cemented sandstone undergoes unstable damage. The change in the acoustic emission entropy value is exactly the opposite of the b value change law. When the weakly cemented sandstone reaches the critical failure state under different dry-wet cycles, the relative stress value is 95%. The test results provide new methods and a basis for the damage evolution mechanism and fracture prediction of weakly cemented sandstone under dry-wet cycles.